From Luxury to Mass Market: How Brand Love and Luxury Perception Drive Purchase Intentions Through TPB - Risky Rahmawati Pinardi; Agung Wahyu Handaru; Agus Wibowo (Journal of Applied Data Sciences, 2026)
This study examines psychological mechanisms shaping consumer purchase intentions for mass market products from former luxury brands. Grounded in the Theory of Planned Behavior and attachment theory, we investigate how luxury brand perception and brand love influence attitudes and subjective norms as antecedents of behavioral intention. Data were collected from 868 Jakarta consumers through an online survey and analyzed using partial least squares structural equation modeling to assess measurement and structural relationships. Results indicate that luxury brand perception exerts significant direct effects on purchase intention and indirect effects mediated specifically through attitude and subjective norm. Brand love influences purchase intention exclusively through these same attitudinal and normative pathways, with no significant direct effect observed. Both attitude and subjective norm significantly mediate the relationships between luxury perception, brand love, and purchase intention. Contrary to expectations, self-referencing does not moderate the attitude intention or subjective norm intention relationships, suggesting limited influence of self-related cognitive processing in this context. Theoretically, this research advances the Theory of Planned Behavior by positioning brand love as an antecedent rather than an outcome of attitudes and subjective norms, thereby integrating emotional attachment as a foundational driver within rational decision frameworks. Managerially, findings suggest that luxury brands entering mass markets should prioritize preserving symbolic heritage and cultivating emotional bonds while leveraging social validation mechanisms to translate brand love into actual purchase behavior. Limitations include the cross-sectional design restricting causal inference and the single culture Jakarta sample limiting generalizability. Future research should employ longitudinal and cross-cultural designs to examine dynamic emotional attachment processes and test model robustness across diverse consumer contexts.